2022
DOI: 10.1186/s12887-022-03213-5
|View full text |Cite
|
Sign up to set email alerts
|

Are children on track with their routine immunization schedule in a fragile and protracted conflict state of South Sudan? A community-based cross-sectional study

Abstract: Objectives The objective of this study was to assess if children aged 0–23 months in a conflict-affected state of South Sudan were on track with their immunization schedule and to identify predisposing factors that affected this study population from being on track with their routine immunization schedule. Design Community-based cross-sectional study using a semi-structured questionnaire. The binary outcome of interest was defined as being on or of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The HP state government also used drum beating for reaching the caregivers during the periodic routine immunization intensification campaign known as Mission Indradhanush. Consistent with the drum beating initiative, Idris et al reported that in the fragile and conflict settings prior notification to the community before conducting the outreach immunization helped in the on-time vaccination of children [10]. Abdur, et al suggested the use of public announcements using loudspeakers to make uneducated caregivers aware of the timely vaccination of children in the hard-to-reach areas [11].…”
Section: Drum Beating-a Useful Alternative Communication Methods To R...mentioning
confidence: 99%
“…The HP state government also used drum beating for reaching the caregivers during the periodic routine immunization intensification campaign known as Mission Indradhanush. Consistent with the drum beating initiative, Idris et al reported that in the fragile and conflict settings prior notification to the community before conducting the outreach immunization helped in the on-time vaccination of children [10]. Abdur, et al suggested the use of public announcements using loudspeakers to make uneducated caregivers aware of the timely vaccination of children in the hard-to-reach areas [11].…”
Section: Drum Beating-a Useful Alternative Communication Methods To R...mentioning
confidence: 99%
“…Defaulters, on the other hand, have recently been defined as a child who is off track with their immunization schedule (18) or a delayed immunized child [ 19 ], who has not received his eligible vaccine dose for 28 days or more of delay according to its country's recommended schedule. Nonetheless, these researchers included children aged 0–23 months in their study [ 18 , 19 ].…”
Section: Evidence Of Mis-usagementioning
confidence: 99%
“… 12 A 2020 community-based cross-sectional study in rural communities in 4 counties of South Sudan’s Western Lakes State found that 75.5% of children were not following the prescribed immunization schedule. 13 The RI schedule in South Sudan covers children aged younger than 1 year but has expanded to children up to age 23 months to account for significant population movement. Additionally, RI for women of childbearing age provides vaccines for tetanus and diphtheria.…”
Section: Introductionmentioning
confidence: 99%